Evaluasi User Experience Game Ragnarok M: Eternal Love dengan Metode Cognitive Walkthrough - Achmad Arif Kusamiaji; Agi Putra Kharisma; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ragnarok M: eternal love is an online game that released on October 30, 2018, is a mobile game version of the Ragnarok computer. Ragnarok is a popular game in Indonesia until now the players in this game reach 62 million people. With it, this game has the potential to attract old and new players to play, even though the platforms are different. So the user experience is important for the success of this game on the market, especially if the application has just been released. Applications that are made poorly and are difficult to use will make it difficult for users to use and learn, so it will rarely be used and not sold in the market. To get a good user experience, an evaluation is necessary. The Cognitive Walkthrough is a user experience evaluation method where evaluators provide scenario-based tasks and questions to users to find problems that interfere with the learning and understanding process. The method is well used in new applications because they can find the cognitive processes of users when they first use the application and get the weakness of it. The results of the evaluation show that the problem that occurs is the lack of understanding of the game in the gameplay tasks, displays that are difficult to understand on the task of logging and hidden key issues in gameplay tasks. Even though there is a problem, the problem is a mild problem that does not affect the main function in the game.